HUBUNGAN ANTARA FAKTOR HOST DAN ENVIRONMENT DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS CILEMBANG KOTA TASIKMALAYA - Hudmawan, Zalfa Azzachra; Abdurrahmat, Asep Suryana; Annashr, Nissa Noor (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Pneumonia is still listed as a major health problem in children in developing countries and is one of the diseases that causes the highest morbidity and mortality in children under five years of age (toddlers). Pneumonia is a form of acute repiratory infection (ARI) that attacks the lungs most often caused by viruses or bacteria. The goal of research to determine the relationship between host and environment factors with the incidence of pneumonia in toddlers. The methode is quantitative using a case control study design with a sample of 55 people. The instrument used is a questionnaire. The sampling technique for the case group was carried out by proportional random sampling and for the control group by simple random sampling. The results bivariate test showed that there a relationship between gender (p=0,039), exclusive breastfeeing (p=0,000), immunization status (p=0,000), family income (p=0,026), mothers education (p=0,032), exposure to smoking (p=0,028), and occupancy density (p=0,016) on the incidence of pneumonia in toddlers. The suggestion is increasing the role of family in supporting toodler health and providing education about healthy home also need to be done by health workers.